Animalscapes and empire: new perspectives on the Iron Age/Romano British transition - Allen, Martyn George (2011)
Human-animal relationships have long existed, across cultures, in many varied forms. The associations between the two are integral to the creation, form, use and perception of landscapes and environments. Despite this, animals are all too often absent from our views of ancient landscapes. Humans experience their diverse environments through a variety of media, and animals regularly play an important role in this type of exchange. Landscape archaeology commonly emphasises the influences of humanity upon the physical world. However, such engagement is rarely unilateral. Whether herding domesticated mammals, hunting quarry, or merely experiencing the range of fauna which populate the world, many of these interactions leave physical traces in the landscape: the form and location of settlements, enclosures, pathways, woodland, pasture, and meadows. Also, in more subtle ways, human and animal actors work together in performances through which people subconsciously generate their perceptions of landscape and environment. These physical and psychological animal landscapes have the potential to inform on human society and ideology. This thesis seeks to utilise zoo archaeological evidence to examine this concept. Animalscape research could be applied to any place or period but as a case study this project will explore, through animal bone analysis, how landscape and environment were used to negotiate cultural identity during the Iron Age/Romano-British transition, a pivotal but poorly understood period in British history.